Effect of physical form and level of alfalfa in corn-based diets on performance of finishing steers - Healy, B.J.; Brandt, Robert T., Jr.; Gramlich, S.M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred forty-four crossbred steers (850 lb) were used to evaluate the effects of physical form and level of average (15% CP) quality alfalfa on performance and carcass traits. Alfalfa hay had been harvested from a common field and alternate bales were either chopped (3 to 4 in. length) or ground and pelleted (3/8 in. pellet). No interactions between alfalfa form and level were detected. Daily gain, daily intake, feed efficiency, and carcass traits were similar for steers fed both alfalfa forms. Steers fed 10% alfalfa consumed 7.2% more feed (P<.03) than those fed 5%. Steers fed 5% alfalfa had marginally improved feed efficiencies, whereas those fed 10% had somewhat greater daily gains. Carcass traits were not affected by level of alfalfa. The incidence and severity of liver abscesses were greater (P<.05) for steers fed 5% alfalfa, indicative of a higher degree of acidosis than for steers fed 10% alfalfa.
Keywords: Beef; Alfalfa; Hay; Pellets; Finishing steers